2005
DOI: 10.1523/jneurosci.1327-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Locomotion with Voluntary Movements in Humans

Abstract: Muscle activity occurring during human locomotion can be accounted for by five basic temporal activation patterns in a variety of locomotion conditions. Here, we examined how these activation patterns interact with muscle activity required for a voluntary movement. Subjects produced a voluntary movement during locomotion, and we examined the resulting kinematics, kinetics, and EMG activity in 16 -31 ipsilateral limb and trunk muscles during the tasks. There were four voluntary tasks added to overground walking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
385
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(428 citation statements)
references
References 52 publications
(80 reference statements)
33
385
1
1
Order By: Relevance
“…It is believed that the number of synergies used by a human being when walking is between 4 and 6 (Allen and Neptune, 2012;Clark et al, 2010;De Groote et al, 2014;Ivanenko et al, 2005Ivanenko et al, , 2004Oliveira et al, 2014). The Variance Accounted For (VAF) between the reconstructed and the original signals is evaluated to select the proper number of modules to be used when factorizing the signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the number of synergies used by a human being when walking is between 4 and 6 (Allen and Neptune, 2012;Clark et al, 2010;De Groote et al, 2014;Ivanenko et al, 2005Ivanenko et al, , 2004Oliveira et al, 2014). The Variance Accounted For (VAF) between the reconstructed and the original signals is evaluated to select the proper number of modules to be used when factorizing the signals.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that there are similarities in the muscle synergies when performing the same movement across subjects. Several authors reported muscle synergies when walking (Clark et al, 2010;Dominici et al, 2011;Ivanenko et al, 2004;Neptune et al, 2009;Oliveira et al, 2014), walking with perturbations (Ivanenko et al, 2005) or performing other tasks (Rugy et al, 2013). Clark et al (2010) applied the muscle synergy analysis in post-stroke injured subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The notion of multi-muscle synergies has been invoked in many studies of postural tasks (Krishnamoorthy et al 2003a(Krishnamoorthy et al ,b, 2004Ivanenko et al 2005Ivanenko et al , 2006 ; Ting and Macpherson 2005;Wang et al 2005Wang et al , 2006Torres-Oviedo et al 2006;Danna-Dos-Santos et al 2007) as a means of reducing (but not eliminating) the notorious redundancy of the multi-muscle system (cf. Bernstein 1967).…”
Section: Introductionmentioning
confidence: 99%
“…At the lower level, muscles form groups, within which their levels of activation co-vary across a wide range of tasks. Such groups have been referred to as muscle modes (M-modes, Krishnamoorthy et al 2003a,b) or muscle synergies (Ivanenko et al 2004(Ivanenko et al , 2005(Ivanenko et al , 2006Ting and Macpherson 2005;Torres-Oviedo and Ting 2007;Saltiel et al 2001;D'Avela et al 2005). At the upper level, the M-modes are considered as the elemental variables, and their co-variation is organized in a task-specific manner to stabilize an important performance variable.…”
Section: Introductionmentioning
confidence: 99%
“…The coordination of the many muscles involved in standing has been viewed as an example of muscle synergies, large groups of muscles united by a common motor goal (Bernstein 1967;Ivanenko et al 2004Ivanenko et al , 2005Ting and Macpherson 2005).…”
Section: Introductionmentioning
confidence: 99%